Ag(i) and Cu(i) cyclic-triimidazole coordination polymers: revealing different deactivation channels for multiple room temperature phosphorescences. Issue 5 (13th January 2021) - Malpicci, Daniele; Lucenti, Elena; Forni, Alessandra; Marinotto, Daniele; Previtali, Andrea; Carlucci, Lucia; Mercandelli, Pierluigi; Botta, Chiara; Righetto, Stefania; Cariati, Elena
Abstract : The photophysics of isostructural Ag(i ) and Cu(i ) 1D and 3D coordination polymers based on cyclic triimidazole reveals excitation wavelength-dependent multiple emissions with different radiative paths according to the coordinated metal. Abstract : The remarkable emissive properties of cyclic triimidazole (TT ), showing crystallization-induced emissive behavior and, in particular, room temperature phosphorescence (RTP), are here combined with its versatility in assembling coordination compounds. A series of Ag(i ) coordination polymers (CPs), comprising a 1D chain ([Ag(TT)I] n, 1-Ag ) and 3D networks ([Ag(TT)Cl] n, 2-Ag, and [Ag3 (TT)4 ] n (NO3 )3 n ·6 n H2 O, 3-Ag ), have been synthesized and their photophysical behavior thoroughly investigated. They show both fluorescence and multiple RTPs, all simultaneously activated but varied in intensity by changing the excitation energy. Based on DFT/TDDFT calculations and analysis of the X-ray crystal structures, the origin of the different phosphorescences has been ascribed to H-aggregation of the ligand (in 1-Ag and 2-Ag ), intermolecular electronic coupling by an extrinsic heavy-atom effect (in 1-Ag ) and ligand-centered emissive states (in all three compounds). Comparison with isostructural 1-Cu and 2-Cu CPs reveals that, different from the Ag(i ) analogues, non-thermally equilibrated XMLCT and ligand-centered emissive states are active. The isostructural Ag(i ) and Cu(i ) compounds show comparable emission efficiency, while the phosphorescence lifetimes are longer for the former (ms regime) than the latter (μs regime). A Quantum Theory of Atoms In Molecules (QTAIM) topological analysis of electron density allows the interpretation of the different nature of the emissive states of Ag(i ) and Cu(i ) compounds on the basis of larger shell-shared character of the Cu–N bond with respect to the Ag–N one.